Kolaborasi pustakawan dan ilmuwan di perguruan tinggi dalam Community Of Practice (CoP) - Kalarensi Naibaho (Al Maktabah, 2015)
Community of Practice (CoP) is one of the communities (research groups) from various disciplines and have an interest in a particular subject. The existence of this CoP is not always permanent. The amount was not observed. Communities can be dispersed when the research is complete, and may be flocking back when they have other interests are the same. CoP presence is not always planned, but its activities must be well planned. According to Weber, a person becomes a member of CoP when she played a man practicing something (practitioners) and interact with fellow members to exchange experiences, learn to solve practical problems, and exchange information. The communication system is similar to the CoP members of the scientific comunication. CoP always associated with learning activities together (collective learning), where the library has an important role. Library as a learning resource provider become an important asset for the CoP. According Pendit (2003) in the context of shared learning, CoP theory to develop a view on access to learning resources and the right to participate in activities of a CoP. Learning resource librarian is what makes it is possible to collaborate with the CoP. Librarians can engage in activities CoP with a role as a facilitator, mediator, and subject specialist, without being a member of the CoP. The existence of a CoP, peripherals process each member is an interesting and unique process. The whole process can be monitored and recorded by the librarian becomes tacit knowledge institution.